Enhancement of Rotator Cuff Healing with Farnesol-Impregnated Gellan Gum/Hyaluronic Acid Hydrogel Membranes in a Rabbit Model - Yen-Hung Lin; Sheng-I Lee; Feng-Huei Lin; Guan-Xuan Wu; Chun-Shien Wu; Shyh-Ming Kuo (MDPI AG, 2021)
Most rotator cuff (RC) tears occur at the bone-tendon interface and cause disability and pain. Farnesol, a sesquiterpene compound, can exert antioxidative and anti-inflammatory effects and promote collagen synthesis. In this rabbit model, either commercial SurgiWrap membrane or hydrogel membranes containing various compositions of gellan gum, hyaluronic acid, and farnesol (hereafter GHF membranes) were applied to the tear site, and the repair of the cuff was examined 2 and 3 weeks afterward. The designed membranes swelled rapidly and adsorbed onto the tear site more readily and closely than the SurgiWrap membrane. The membranes degraded slowly and functioned as both a barrier and a vehicle of slow farnesol release during the repair period. Farnesol enhanced collagen production in myoblasts and tenocytes, and interleukin 6 and tumor necrosis factor α levels were modulated. Gross observations and histological examinations indicated that the GHF membranes impregnated with 4 mM farnesol resulted in superior RC repair. In sum, the slow release of farnesol from hydrogel membranes can be beneficial in the repair of RC injuries.